2018
DOI: 10.1038/s41598-018-25059-7
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking, localization and degradation of the Na+,HCO3− co-transporter NBCn1 in kidney and breast epithelial cells

Abstract: The Na+;HCO3− co-transporter NBCn1 (SLC4A7) is a major regulator of intracellular pH yet its trafficking and turnover are essentially unstudied. Here, we used MDCK-II and MCF-7 cells to investigate these processes in epithelial cells. GFP-NBCn1 membrane localization was abolished by truncation of the full NBCn1 C-terminal tail (C-tail) yet did not require the C-terminal PDZ-binding motif (ETSL). Glutathione-S-Transferase-pulldown of the C-tail followed by mass spectrometry analysis revealed putative interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 65 publications
3
18
0
Order By: Relevance
“…Role (s) for previously described cell cycle regulatory signaling pathways [40] seems likely, however, also the pH changes during the cell cycle could be involved. For example, ChIP-seq analysis has shown that the NHE1 promoter interacts with, among many others, the transcription factors E2F1 and Egr-1 [60]. E2F1 is a major regulator of cell cycle dependent transcription [40], and it is interesting to note that its expression profile as shown in this study fits well with the NHE1 expression profile during the cell cycle (compare Figures 4(a) and 6(b)).…”
Section: Discussionsupporting
confidence: 69%
“…Role (s) for previously described cell cycle regulatory signaling pathways [40] seems likely, however, also the pH changes during the cell cycle could be involved. For example, ChIP-seq analysis has shown that the NHE1 promoter interacts with, among many others, the transcription factors E2F1 and Egr-1 [60]. E2F1 is a major regulator of cell cycle dependent transcription [40], and it is interesting to note that its expression profile as shown in this study fits well with the NHE1 expression profile during the cell cycle (compare Figures 4(a) and 6(b)).…”
Section: Discussionsupporting
confidence: 69%
“…As we predicted from our RACK1 interaction analysis (Olesen et al, 2018), truncation of the entire C-terminal distal to α-helix I (i.e. 1139-1254) had no effect on NBCn1 plasma membrane expression (Fig.…”
Section: A Short Proximal C-terminal α-Helical Motif Is Essential For...supporting
confidence: 72%
“…Whereas the short delay from tissue isolation to functional evaluation is a unique strength of the current study—because it minimizes the risk of phenotypical changes and thereby strengthens the connection to the clinical condition—it limits the experimental possibilities for detailed mechanistic and molecular studies. The experimental setup allows for manipulation and precise control of the buffer compositions; but with half-lives of protein degradation of 76 and 48 hr for NBCn1 and NHE1, respectively ( Olesen et al, 2018 ), we cannot realistically reduce overall cellular protein levels by interfering with their expression—e.g., by RNAi knockdown technologies ( Boedtkjer et al, 2006 )—in the human biopsy material. Also, the available pharmacological options are too unspecific and without selectivity for individual Na + ,HCO 3 – cotransporters ( Boedtkjer et al, 2016 ; Boedtkjer et al, 2012 ; Larsen et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%